Genetic variants of gonadotrophins and their receptors: Impact on the diagnosis and management of the infertile patient. Issue 1 (January 2022) - Rivero-Müller, Adolfo; Huhtaniemi, Ilpo
Abstract : This narrative review is concerned with genetic variants of the genes encoding gonadotrophin subunits and their receptors, as well as their implications into the diagnosis and treatment of infertility. We first review briefly the basics of molecular biology and biochemistry of gonadotrophin and gonadotrophin receptor structure and function, then describe the phenotypic effects of polymorphisms and mutations of these genes, followed by diagnostic aspects. We will then summarise the information that inactivating gonadotrophin receptor mutations have provided about the controversial topic of extragonadal gonadotrophin action. Finally, we will close with the current and future therapeutic approaches on patients with gonadotrophin and their receptor mutations.